2017
DOI: 10.1007/s00423-017-1573-x
|View full text |Cite
|
Sign up to set email alerts
|

Esophagectomy for cancer in octogenarians: should we do it?

Abstract: Postoperative mortality, morbidity, and length of stay in octogenarians are comparable to younger patients, while the overall survival is worse. With appropriate patient selection, good outcomes can be accomplished in octogenarians undergoing esophagectomy for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…Despite acceptable short-term outcomes, the length of hospital stay was long (mean, 28.1 and 26.0 days in the non-elderly and elderly groups). In Japan, the length of hospital stay tends to be much longer than that in the Western countries because of the difference in social and medical systems [2,5,7,8,19]. Patients typically return home to daily life directly after discharge so that they stay at the hospital until they get substantial recovery, fair oral intake, and removal of all drainage tubes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite acceptable short-term outcomes, the length of hospital stay was long (mean, 28.1 and 26.0 days in the non-elderly and elderly groups). In Japan, the length of hospital stay tends to be much longer than that in the Western countries because of the difference in social and medical systems [2,5,7,8,19]. Patients typically return home to daily life directly after discharge so that they stay at the hospital until they get substantial recovery, fair oral intake, and removal of all drainage tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is the sixth on the list of cancers with the highest mortality rates [1]. Moreover, the increasing general life expectancy leads to a larger number of elderly patients diagnosed as esophageal cancer [2]. Although esophagectomy is still positioned as the cornerstone treatment for esophageal cancer, it is associated with high morbidity and mortality rates for elderly patients despite recent advances in the surgical practice [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Several patient characteristics may influence the outcomes following surgery for oesophageal cancer. Older age is a prognostic factor, but its influence has declined with more specialised surgery and is more evident only after the age of 80 years, and rather related to co-morbidities than age itself 160162. Higher Charlson Co-morbidity Index (which assigns a score based on the presence and severity of 22 comorbid conditions) and previous heart conditions seem to reduce the prognosis after oesophageal cancer surgery, and co-morbidities may also negatively influence the long-term health-related quality of life following oesophagectomy 8,162.…”
Section: Managementmentioning
confidence: 99%
“…However, previ-ous reports have shown that elderly patients have similar morbidity and mortality rates than younger patients. [8][9][10] For instance, Ruol et al 9 compared the postoperative outcomes of 159 patients q70 years old and 580 patients <70 years old at a single institution and found that the rates of overall morbidity (49.1% versus 48.6%), in-hospital mortality (1.9% versus 2.7%), and 30-day mortality (1.9% versus 1.9%) were similar in both the groups. Similarly, Paulus et al 10 reported that postoperative morbidity, mortality, and length of stay in octogenarians were comparable to younger patients.…”
Section: Discussionmentioning
confidence: 99%